The nomenclature of duct-dependent lesions, broadening the categories for a better clinical practice - AbdelMassih, Antoine; George, Acsah; Mohammad, Dima; Ansari, Fazeela; Prachith, Soumya (Pediatric Sciences Journal, 2024)
Ductus arteriosus-dependent lesion includes two well-established categories, the right sided obstructive lesions such as pulmonary atresia (duct-dependent pulmonary circulation) and the left sided obstructive (duct-dependent systemic circulation) lesions ranging from hypoplastic left heart syndrome to severe preductal coarctation. Dextro-transposition of the great arteries (D-TGA) lies in a gray area, as it is considered by some old classifications as a duct-dependent pulmonary circulation lesion and by others as a new category of duct-dependent mixing lesion. We suggest adding a new functional classification, where the category of duct dependent systemic circulation/perfusion remains unchanged, and whereby duct-dependent pulmonary lesions are renamed into a broader category of duct dependent oxygenation with two sub-categories: mixing defects such as D-TGA, and defective oxygenation due to right sided obstructive lesions such as pulmonary atresia. We believe that this re-classification will cover the anatomical aspects and clinical implications of these lesions and will facilitate their management by the residents which are the primary encounter physicians in many of the developing countries.